Distribution of heavy metal concentrations (Cd, Cu, Ni, Fe And Zn) in the different soft tissues and shells of wild mussels Perna viridis collected from Bagan Tiang and Kuala Kedah - Yap, Chee Kong; Hatta, Y.; Edward, Franklin Berandah; Tan, Soon Guan (Malaysian Society of Applied Biology, 2008)
Concentrations of Cd, Cu, Ni, Fe and Zn were determined in the Perna viridis populations collected in April 2005 from Bagan Tiang and Kuala Kedah. The ranges of Cd, Cu and Zn found in this study were lower than the maximum permissible limits set by Malaysian Food Regulations 1985 and other established guidelines. Therefore, the consumption of wild mussels collected from Bagan Tiang and Kuala Kedah should pose no acute toxicological risks of Cd, Cu and Zn to humans. Despite the apparently low concentrations of Cd, Cu, Fe, Ni and Zn in the different soft tissues of P. viridis collected from Bagan Tiang and Kuala Kedah, from a public health risk perspective, the data suggested the need for continued monitoring of heavy metal pollution in the mussels.